U.S. Overseas Military Presence - Davis, Lynn E.; Pettyjohn, Stacie L.; Sisson, Melanie W.; Worman, Stephen M.; McNerney, Michael J. (RAND Corporation, 2023)
The role of the United States and its global military presence are under debate in the face of changing strategic and economic realities. The authors present a menu of global postures and compare them in terms of the U.S. Air Force bases, combat forces, active-duty personnel, and base operating costs. Ultimately, the choice will depend on perspectives on the role overseas military presence can play in achieving U.S. global security interests.